Successful living donor liver transplant in a very small child - Vijay Kumar (Indian Journal of Anaesthesia, 2010)
Liver transplantation in small children poses perioperative challenges that are different from those seen in adults. We present our successful anaesthetic experience in a 7-month-old infant who has been the youngest case of successful living donor liver transplant performed in our institution till the day this article was being prepared.